An exploratory study on the knowledge management practices of duly-recognized school of library and information studies student organizations - Luna, Adrian Philip B. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Over the past decade, there has been an increase in interest with the study and management of knowledge. However, while the practice of managing knowledge is prevalent in large companies and organizations, little is known about the extent of knowledge management in student organizations. This study sought to find out the extent to which the student organizations of the UP School of Library and Information. Studies manage their knowledge. Understanding their processes can lead to better management of their knowledge assets, thus promoting organizational learning. The respondents were interviewed regarding their practices. The results show that these organizations have set in place various processes in which to manage their knowledge. They also have similarities regarding their processes which came from their previous interactions with other organizations. However, they lack essential parts in the knowledge management cycle. These issues arise from the lack of knowledge regarding the management of knowledge assets. Furthermore, the lack of a proper refinement phase hinders the organizations from fully utilizing their knowledge assets to its utmost potential.